2014
DOI: 10.1002/ange.201405531
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Hydrogenation Catalyzed by an Air‐Stable Borane: Use of Solvent as a Frustrated Lewis Base

Abstract: In recent years frustrated Lewis pairs (FLPs) have been shown to be effective metal-free catalysts for the hydrogenation of many unsaturated substrates. Even so, limited functional-group tolerance restricts the range of solvents in which FLP-mediated reactions can be performed, with all FLP-mediated hydrogenations reported to date carried out in non-donor hydrocarbon or chlorinated solvents. Herein we report that the bulky Lewis acids B(C 6 Cl 5 ) x (C 6 F 5 ) 3Àx (x = 0-3) are capable of heterolytic H 2 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…[1][2][3][4] Cooperative catalysts consisting of "soft" organometallic Lewis acids and stronger Brønsted bases such as ShibasakisC u(Biphep)/Bartons base catalysts C3 and Tr ostsZ n(ProPhenol) complex C4 have been shown to overcome mutual quenching and promote Mannich-type reactions with less acidic 7-azaindolineamides [2e,5] and ketones, [2d, 6] respectively.D espite such notable progress,t here exist few organic cooperative acid/ base catalysts capable of promoting the direct Mannich(-type) reaction of mono-carbonyl pronucleophiles. [9,10] These unquenched acid/base complexes are capable of activating otherwise unreactive small molecules such as H 2 and CO 2 . [9,10] These unquenched acid/base complexes are capable of activating otherwise unreactive small molecules such as H 2 and CO 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4] Cooperative catalysts consisting of "soft" organometallic Lewis acids and stronger Brønsted bases such as ShibasakisC u(Biphep)/Bartons base catalysts C3 and Tr ostsZ n(ProPhenol) complex C4 have been shown to overcome mutual quenching and promote Mannich-type reactions with less acidic 7-azaindolineamides [2e,5] and ketones, [2d, 6] respectively.D espite such notable progress,t here exist few organic cooperative acid/ base catalysts capable of promoting the direct Mannich(-type) reaction of mono-carbonyl pronucleophiles. [9,10] These unquenched acid/base complexes are capable of activating otherwise unreactive small molecules such as H 2 and CO 2 . [9,10] These unquenched acid/base complexes are capable of activating otherwise unreactive small molecules such as H 2 and CO 2 .…”
mentioning
confidence: 99%
“…[9,10] These unquenched acid/base complexes are capable of activating otherwise unreactive small molecules such as H 2 and CO 2 . [9][10][11][12] Our laboratory has described the development of strongly acidic B(C 6 F 5 ) 3 and chiral diamine catalysts for direct enantioselective CÀNb ond forming reactions between ketones and dialkyl azodicarboxylates. [9][10][11][12] Our laboratory has described the development of strongly acidic B(C 6 F 5 ) 3 and chiral diamine catalysts for direct enantioselective CÀNb ond forming reactions between ketones and dialkyl azodicarboxylates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Ashley et al . reported that hydrogenation of furan derivatives under the frustrated Lewis pairs catalysis using (B(C 6 Cl 5 )(C 6 F 5 ) 2 ) delivers reduced tetrahydrofuran compounds23. Despite of such progresses on furan transformation reactions, there have been no developments thus far for the selective conversion of furans to ring-opened products bearing a sp 3 C−Si bond at ambient conditions.…”
mentioning
confidence: 99%